1986
DOI: 10.1523/jneurosci.06-09-02509.1986
|View full text |Cite
|
Sign up to set email alerts
|

Actions of opioids on primate spinothalamic tract neurons

Abstract: The effects of iontophoretically applied opiates were tested on 24 spinothalamic tract cells in 12 anesthetized monkeys. The drugs used were chosen because of their agonist actions on different classes of opiate receptors (mu, morphine; kappa, dynorphin; delta, methionine enkephalinamide; sigma, N-allylnormetazocine or SKF 10047 and phencyclidine). The actions of the opiate drugs were generally inhibitory, although excitatory or mixed effects were sometimes seen, especially with morphine and dynorphin. Drug ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 57 publications
(57 reference statements)
1
18
0
Order By: Relevance
“…The effects of pruritogens on the neurons examined in this previous study were not determined and thus neurons could not be categorized as pruriceptive or not. We have found that a similar fraction (∼30%) of primate STT neurons is pruriceptive (Davidson et al, 2012), suggesting that the STT neurons activated by morphine in the study by Willcockson et al (1986) may well have been pruriceptive. If this conclusion is correct, it would suggest that morphine may activate pruriceptive and inhibit nociceptive STT neurons in primates as it does VTT neurons in rats.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The effects of pruritogens on the neurons examined in this previous study were not determined and thus neurons could not be categorized as pruriceptive or not. We have found that a similar fraction (∼30%) of primate STT neurons is pruriceptive (Davidson et al, 2012), suggesting that the STT neurons activated by morphine in the study by Willcockson et al (1986) may well have been pruriceptive. If this conclusion is correct, it would suggest that morphine may activate pruriceptive and inhibit nociceptive STT neurons in primates as it does VTT neurons in rats.…”
Section: Discussionmentioning
confidence: 67%
“…There is a great deal of evidence supporting an inhibitory role for morphine on nociceptive spinal neurons, including projection neurons; supporting data have come from a variety of species, experimental preparations, and routes of administration (Satoh et al, 1971; Kitihata et al, 1974; Le Bars et al, 1975, 1976; Yoshimura and North, 1983; Hylden and Wilcox, 1986; Willcockson et al, 1986; Craig and Serrano, 1994; Chen and Pan, 2002). However, morphine can also cause excitation of ongoing activity in some cells in the dorsal horn (Jones et al, 1990; Craig and Hunsley, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide dynamic range (WDR) neurons in the dorsal horn represent an important component in spinal pain transmission and a target for opioid actions (Homma et al, 1983;Collins et al, 1984;Willcockson et al, 1986;Wang et al, 1996;You et al, 2003). Importantly, WDR neurons are readily sensitized by intense noxious inputs, and they exhibit a frequency-dependent, progressive increase in the neuronal excitability in response to repeated electrical activation of afferent C-fibers (windup) (Mendell and Wall, 1965;Herrero et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One important location for the action of opioids is the dorsal horn of spinal cord where opioid receptors are found on both spinal interneurons and on the terminals of the primary afferent nociceptors whose cell bodies are in the dorsal root ganglia (DRG). 3,4 In vitro opioids produce a direct inhibitory effect on the electrical activity of spinothalamic projection neurons of dorsal horn or trigeminal nucleus, [5][6][7] and act presynaptically to inhibit release of neurotransmitter from DRG neurons. [8][9][10][11] Intrathecal administration of morphine inhibits the release of substance P by the primary afferent nociceptor in vivo, 12 which correlates with the efficacy of intrathecal opiates that are used in clinical applications.…”
Section: Introductionmentioning
confidence: 99%